The impact of financial development on economic growth in Nigeria: An ARDL analysis - Eugene Iheanacho (Economies, 2016)
This study empirically examines the relationship between financial intermediary development and economic growth in Nigeria over the period 1981-2011 using the auto-regressive distributed lag (ARDL) approach to co-integration analysis. The results show that the relationship between financial development and economic growth in Nigeria is not significantly different from what has been observed generally in oil-dependent economies. The relationship between financial intermediary development and economic growth in Nigeria is found to be insignificantly negative in the long-run and significantly negative in the short-run. The results highlight the dominant role of the oil sector in economic activities in Nigeria.
Keywords: G20; O11; Q32; 330; financial development; economic growth; oil price; oil-dependent economies; Nigeria; ARDL